Sera Neutralizing Activities Against Severe Acute Respiratory Syndrome Coronavirus 2 and Multiple Variants 6 Months After Hospitalization for Coronavirus Disease 2019. (14th April 2021) - Betton, Maureen; Livrozet, Marine; Planas, Delphine; Fayol, Antoine; Monel, Blandine; Védie, Benoit; Bruel, Timothée; Tartour, Eric; Robillard, Nicolas; Manuguerra, Jean-Claude; Blanchard, Anne; Ghosn, Jade; et al.
Abstract: Background: Humoral response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurs within the first weeks after coronavirus disease 2019 (COVID-19). Those antibodies exert a neutralizing activity against SARS-CoV-2, whose evolution over time after COVID-19 as well as efficiency against novel variants are poorly characterized. Methods: In this prospective study, sera of 107 patients hospitalized with COVID-19 were collected at 3 and 6 months postinfection. We performed quantitative neutralization experiments on top of high-throughput serological assays evaluating anti-spike (S) and anti-nucleocapsid (NP) immunoglobulin G (IgG). Results: Levels of seroneutralization and IgG rates against the ancestral strain decreased significantly over time. After 6 months, 2.8% of the patients had a negative serological status for both anti-S and anti-NP IgG. However, all sera had a persistent and effective neutralizing effect against SARS-CoV-2. IgG levels correlated with seroneutralization, and this correlation was stronger for anti-S than for anti-NP antibodies. The level of seroneutralization quantified at 6 months correlated with markers of initial severity, notably admission to intensive care units and the need for mechanical invasive ventilation. In addition, sera collected at 6 months were tested against multiple SARS-CoV-2 variants and showed efficient neutralizing effects against the D614G, B.1.1.7, and P.1 variants but significantly weaker activity against the B.1.351 variant. Conclusions: Decrease in IgG rates and serological assays becoming negative did not imply loss of neutralizing capacity. Our results indicate a sustained humoral response against the ancestral strain and the D614G, B.1.1.7, and P.1 variants for at least 6 months in patients previously hospitalized for COVID-19. A weaker protection was, however, observed for the B.1.351 variant. Abstract : Anti–SARS-CoV-2 antibodies decline over time. In patients previously hospitalized for COVID-19, we found a sustained humoral response for at least 6 months. The antibodies cross-react and should confer a similar protection against emerging variants, with the notable exception of the B.1.351 variant.